Two Approaches to Information Security Doctoral Research - Armstrong, Helen (IFIP TC11.8, 2011)
Researchers embarking upon doctoral research in information security face numerous challenges at the commencement of their studies. Students often face confusion as they consider where to start and how to progress. The objectives of the research need to be clearly defined before commencing the project. The research questions, methodology, data and analysis are inextricably tied to the objectives, and as such a top-down approach is recommended. This paper discusses two approaches to doctoral research, top-down and bottom-up. The paper is designed to guide students at the commencement of their information security doctoral research. These guidelines may also be of value to the supervisor.